ONCE DAILY GENTAMICIN DOSE BANDING IN NEWBORNS WITH SIGNS OF EARLY ONSET OF NEONATAL SEPSIS (EONS), BASED ON INITIAL BIRTH WEIGHT AND GESTATIONAL AGE. Issue 9 (17th August 2016) - Windscheif, Paul-Michael; Welsh, Rhoda; Smith, Laura; Nicoll, Ian; Anthony, Mark
Abstract : Aim: Prospective assessment of safety of dose banding of once daily gentamicin in newborns with signs of EONS in their first days of life. Method: All neonates admitted on the level-3 neonatal unit, with at least three consecutive once daily gentamicin doses, started no later than 48 hrs after birth were included. The dose was based on initial birth weight and not adjusted to daily changes of the bodyweight(W). A gentamicin trough level of 2 mg/L was permitted. Neonates with hypoxic ischaemic encephalopathy at birth were not started on a gentamicin regimen. Data was taken from a database system registered as a service evaluation. Of more than 1200 admitted neonates eighty nine (60 boys, 29 girls; born between Feb 2014 and Jul 2015) received at least three consecutive gentamicin doses for EONS soon after birth (within first 24 hrs: 96.6%), while the majority of antibiotic courses started with a gentamicin regimen were stopped within 36 hrs. 23 (25.8%) neonates with a gestational age (GA) of less than 30 weeks started on 5 mg/kg 48-hourly. Neonates 30 weeks and older started on weight based dosing range: Up to 3 kg: 48 (53.9%) neonates on 5 mg/kg 24 hourly. Between 3–3.5 kg: 13 (14.6%) at fixed 15 mg 24 hourly; between 3.5–4 kg: 5 (5.6%) neonates at fixed 17.5 mg 24 hourly. The first trough level (95.5%) was taken before the third dose. Daily weight (W) was recorded. Routine blood samples was recorded including creatinine, C-reactive protein and a routine sample was sent for investigation of bacterial growth. Results: The first trough level for neonates up to 30 weeks on 48 hourly regimen (GA-mean 27, range 24–29; W-mean 0.96 kg, range 0.54–1.4 kg; W-change 3.9%) was for all less than 2 mg/L (mean 0.66 mg/L, range 0.2–1.3). For neonates 30 weeks and older, up to 3 kg: (GA-mean 34, range 30–41; W-mean 2.16 kg, range 1.09–2.86 kg; W-change 2.9%) on 24 hourly regimen the level was for 37(82%) up 2 mg/L (mean 1.6 mg/L, range 0.2–2; for 3 cases no level; eight cases 2 up to 3 mg/L of which 3 results cannot be explained with change of a disease status). Neonates between 3–3.5 kg: (GA-mean 38, range 33–42; W-mean 3.3 kg, range 3–3.48 kg; W-change 0.96%) on 24 hourly regimen: all except for one less than 2 mg/L (mean 1.3 mg/L, range 0.4–2; one at 2.7 with hyperinsulinaemia). Between 3.5–4 kg: (GA-mean 39, range 36–41; W-mean 3.78 kg, range 3.6–3.9 kg; W-change 1.3%) on 24 hourly regimen: all less than 2 mg/L (mean 1.1 mg/L, range 0.4–1.7). None of the samples for 73(82%) neonates sent for bacterial investigation showed bacterial growth over 5 days. Conclusion: Dose banding for gentamicin in EONS is a promising safe option for dosing neonates. There needs to be a revision and re-evaluation in context of the disease profile of the population of a newborn unit as indicated by results for dosing neonates 30 weeks and older but less than 3 kg.